Peran Tenaga Teknis Kefarmasian dalam Pelayanan Kefarmasian (Pengelolaan Sediaan Farmasi dan Farmasi Klinik) - Muhammad Ikhsan (Syntax Corporation Indonesia, 2022)
Tenaga Teknis Kefarmasian (TTK) are health workers who have the authority and competence in assisting the pharmacist profession in providing clinical pharmacy services at pharmacies. Pharmacists in performing clinical pharmacy services have limited authority. The services provided by TTK are under the supervision and responsibility of the pharmacist. This study aims to figure the role of TTK in providing pharmaceutical services in pharmacies. Data analysis was carried out descriptively and presented in the form of tables and narratives. This research is non-experimental descriptive research. Samples were taken as many as 42 pharmacies from 72 pharmacies in the Tegal City based on a random sampling method with simple random sampling. Data were collected through questionnaires filled out by respondents. The results showed that the role of TTK in pharmaceutical preparations’ management activities in Tegal City pharmacies had not been implemented optimally, especially on planning indicators, the average role of TTK in the management of pharmaceutical preparation was 59.1%. The role of TTK in clinical pharmacy services has been carried out well. The average role of TTK in clinical pharmacy services is 86.9%. Evaluation of pharmaceutical services is still less than ideal, indicated by 16.6% of pharmacies that already have standard operating procedures